2018
DOI: 10.1186/s12935-018-0596-x
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured lipid carriers for MicroRNA delivery in tumor gene therapy

Abstract: MicroRNAs (miRNAs), which are endogenous about 20–23 nucleotides non-coding RNAs, have been acted as post-transcriptional regulators of gene expression. Current studies demonstrated that miRNAs are promising candidates for tumor gene therapy because of their important biological functions in tumor cell proliferation, metastasis, apoptosis, and drug resistance. As an important delivery system, nanostructured lipid carriers (NLCs) have great potential in tumor gene therapy, particularly for miRNA delivery, due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…Secondly, miRNAs can also affect tissue microenvironment through modulation of different type of cells and unlike cancer drugs, miRNAs usually does not have cytotoxicity to normal cells . Thirdly, miRNAs showed reduced immune response and low toxicity when compared with lentivirus‐ or protein‐based gene therapy . Our results demonstrated for the first time that miR‐183 injection treatment may serve as an effective therapeutic treatment for reducing pathologic features of SLE patients.…”
Section: Resultsmentioning
confidence: 79%
“…Secondly, miRNAs can also affect tissue microenvironment through modulation of different type of cells and unlike cancer drugs, miRNAs usually does not have cytotoxicity to normal cells . Thirdly, miRNAs showed reduced immune response and low toxicity when compared with lentivirus‐ or protein‐based gene therapy . Our results demonstrated for the first time that miR‐183 injection treatment may serve as an effective therapeutic treatment for reducing pathologic features of SLE patients.…”
Section: Resultsmentioning
confidence: 79%
“…This may offer a greater opportunity to manage a wider variety of tumors. In fact, it was reported that NLCs can serve as a novel vector in gene therapy for lung cancer [160,161]. In addition, the lack of critical analysis on the safety of NLCs as drug carriers presents another major concern.…”
Section: Future Directionsmentioning
confidence: 99%
“…miRNAs can easily be transferred to cells and tissues using liposomes [102,125]. Liposomes are composed of cationic lipids structurally characterized by an hydrophobic moiety and a positively charged cationic head; nucleic acids naturally binds to liposomes through their phosphate-generated negative charge [126].…”
Section: Organic Nanoparticles (Nps)mentioning
confidence: 99%